Seasonal changes in free 25-(OH)D and vitamin D metabolite ratios and their relationship with psychophysical stress markers in male professional football players - Książek, Anna; Zagrodna, Aleksandra; Lombardi, Giovanni; Słowińska-Lisowska, Małgorzata (Frontiers in Physiology, 2023)
Novel markers of vitamin D status are currently being investigated, including free 25-(OH)D (25-(OH)DF) and the vitamin D metabolite ratio (24,25-(OH)2D3:25-(OH)D3; VMR). The VMR may provide additional functional information on vitamin D metabolism in athletes. Therefore, the main objective of the current study was to evaluate 25-(OH)DF, bioavailable 25-(OH)D (25-(OH)DB), VMR, and psychophysical stress markers during different training periods over a half-season. The second aim was to assess the association between vitamin D binding protein (VDBP), total and free 25-(OH)D, VMRs, and psychophysical stress markers in professional football players. Moreover, we examined the relationship between 25-(OH)D3 and vitamin D metabolites (24,25-(OH)2D3, 3-epi-25-(OH)D3) to determine if training loads in different training periods influenced the vitamin D metabolome. Twenty professional football players were tested at six different time points across half a year (V1 – June; V2 – July; V3 – August; V4 – October; V5 – December; V6 – January). Analyses indicated a significant seasonal rhythm for VDBP, and total 25-(OH)D (25-(OH)DT), 25-(OH)DB, 24,25-(OH)2D3, 3-epi-25-(OH)D3, 25-(OH)D3:24,25-(OH)2D3, and 24,25-(OH)2D3:25-(OH)D3 VMRs throughout the training period. No correlation was detected between 25-(OH)DT, 25-(OH)DB, 25-(OH)DF, vitamin D metabolites, VMRs, VDBP, and ferritin, liver enzymes (aspartate transaminase [AST] and alanine transaminase [ALT]), creatine kinase (CK), cortisol, testosterone, and testosterone-to-cortisol ratio (T/C) in each period (V1-V6). However, there was a strong statistically significant correlation between 25-(OH)D3 and 24,25-(OH)D3 in each training period. In conclusion, a seasonal rhythm was present for VDBP, 25-(OH)DT, 25-(OH)DB, vitamin D metabolites (24,25-(OH)2D3, 3-epi-25-(OH)D3), and VMRs (25-(OH)D3:24,25-(OH)2D3, 25-(OH)D3:3-epi-25-(OH)D3). However, no rhythm was detected for 25-(OH)DF and markers of psychophysical stress (ferritin, liver enzymes, CK, testosterone, cortisol, and T/C ratio). Moreover, the relationships between free and total 25-(OH)D with psychophysical stress markers did not demonstrate the superiority of free over total measurements. Furthermore, training loads in different training periods did not affect resting vitamin D metabolite concentrations in football players.